Importance of ice for the «White Olympics» - A. F. Renkel (Лëд и снег, 2016)
Organization of any winter Olympic game, often called as «White Olympics», requires interfacing between sports, technology and glaciology. History of the Olympic winter games and the Norwegian figure skater Sonia Henie, first and the only three-time Olympic champion (1928, 1932, 1936) in ladies figure skating, is presented in the article. Leaving the amateurish sport, Henie became a Hollywood star of the ballet on ice. She was introduced to the inventor Frank Zamboni, who created the ice re-surfacer (the ice-cleaning combine) to restore the ice on skating rinks. Using the combine by Henie during her tours in the United States served to advertise this machine, and the name Zamboni had become a trademark for machines «Zamboni».